2020
DOI: 10.1101/2020.08.27.270223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The novel roles of choline transporter-like 1 and 2 in ethanolamine transport

Abstract: We examined a novel function of mammalian Choline-Transporter-Like proteins CTL1/SLC44A1 and CTL2/SLC44A2 in ethanolamine transport. We established two distinct ethanolamine transport systems of a high affinity (K1 = 55.6 - 66.5 μM), mediated by CTL1, and of a low affinity (K2 = 275 - 299 μM), mediated by CTL2. Both types of transport are Na+-independent and mediated in a pH dependent manner, as expected for ethanolamine/H+ antiporters. Primary human fibroblasts with separate frameshift mutations (M1= SLC44A1Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…To confirm this, we first quantified natural choline extracted from cytoplasm using a choline oxidase-mediated coupled enzyme assay, which revealed that the loss of FLVCR1 dramatically reduced the amount of endogenous choline inside cells (by nearly 80%) (Figure 4D). Note that these phenotypes of FLVCR-KO (decrease in PC synthesis and choline uptake) are the same phenotypes associated with major choline transporter inhibition (Taylor et al, 2021). Moreover, we found that the lower PC labeling intensity in FLVCR1-KO cells was partially restored by re-expression of FLVCR1 and completely rescued by overexpression of SLC5A7 (a high affinity choline transporter specifically expressed in cholinergic neurons) (Okuda et al, 2000); whereas overexpression of PCYT1A had little effect (Figure 4E).…”
Section: Genome-scale Pooled Crispr-ko Screens Focusing On Pc Biosynt...supporting
confidence: 58%
“…To confirm this, we first quantified natural choline extracted from cytoplasm using a choline oxidase-mediated coupled enzyme assay, which revealed that the loss of FLVCR1 dramatically reduced the amount of endogenous choline inside cells (by nearly 80%) (Figure 4D). Note that these phenotypes of FLVCR-KO (decrease in PC synthesis and choline uptake) are the same phenotypes associated with major choline transporter inhibition (Taylor et al, 2021). Moreover, we found that the lower PC labeling intensity in FLVCR1-KO cells was partially restored by re-expression of FLVCR1 and completely rescued by overexpression of SLC5A7 (a high affinity choline transporter specifically expressed in cholinergic neurons) (Okuda et al, 2000); whereas overexpression of PCYT1A had little effect (Figure 4E).…”
Section: Genome-scale Pooled Crispr-ko Screens Focusing On Pc Biosynt...supporting
confidence: 58%
“…PC remained constant due to reduced PC degradation by PSS1 and increased formation by PE methylation [7]. Furthermore, we recently discovered that CTL1 also transport ethanolamine for PE synthesis, and that disruption in the PE homeostasis and consequently involving other PLs is indicative of an intricate internal system to maintain membrane PL balance [72].…”
Section: Iron Accumulation and Oxidative Stressmentioning
confidence: 99%
“…Recently, we identified a new role for CTL1/SLC44A1 and CTL2/SLC44A2 proteins in transporting ethanolamine for PE synthesis. Therefore, since CTL1/2 transport plasma membrane choline and ethanolamine, they directly control PC and PE homeostasis and their membrane ratio [72]. Both CTL1 and CTL2 additionally localize and transport choline and ethanolamine in the mitochondria yet their role in the mitochondria is not completely clear [72].…”
Section: The Critical Regulators Of Pls Synthesis In the Nervous Systemmentioning
confidence: 99%